2011
DOI: 10.1097/mop.0b013e32834aa583
|View full text |Cite
|
Sign up to set email alerts
|

Impact of congenital heart disease on fetal brain development and injury

Abstract: Neurodevelopmental evaluation preoperatively and postoperatively in CHD patients should be standard practice, not only to identify those with impairments who would benefit from intervention services but also to identify risk factors and strategies to optimize outcome. Fetal management and intervention strategies for specific defects may ultimately play a role in improving in-utero hemodynamics and increasing cerebral oxygen delivery to enhance brain development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
87
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(88 citation statements)
references
References 93 publications
0
87
1
Order By: Relevance
“…Various cardiovascular developmental abnormalities, such as ventricular septal defect, atrial septal defect, tetralogy of Fallot, patent ductus arteriosis, atrioventricular septal defect, double outlet right ventricle, pulmonary stenosis, and transposition of great arteries, may occur individually or in combination. These anomalies may result in degraded quality of life, delayed fetal brain development, cardiac enlargement or hypertrophy, pulmonary hypertension, infective endocarditis, thromboembolism, Eisenmenger's syndrome, congestive heart failure, arrhythmias, as well as sudden cardiac death in the absence of surgical or catheter-based repairs (4)(5)(6)(7)(8)(9)(10). Despite the high prevalence and significant clinical importance, the molecular mechanism of CHD remains poorly understood (11).…”
Section: Introductionmentioning
confidence: 99%
“…Various cardiovascular developmental abnormalities, such as ventricular septal defect, atrial septal defect, tetralogy of Fallot, patent ductus arteriosis, atrioventricular septal defect, double outlet right ventricle, pulmonary stenosis, and transposition of great arteries, may occur individually or in combination. These anomalies may result in degraded quality of life, delayed fetal brain development, cardiac enlargement or hypertrophy, pulmonary hypertension, infective endocarditis, thromboembolism, Eisenmenger's syndrome, congestive heart failure, arrhythmias, as well as sudden cardiac death in the absence of surgical or catheter-based repairs (4)(5)(6)(7)(8)(9)(10). Despite the high prevalence and significant clinical importance, the molecular mechanism of CHD remains poorly understood (11).…”
Section: Introductionmentioning
confidence: 99%
“…An explanation for the interchangeable cerebral rSO 2 and FTOE values in infants with antegrade and infants with retrograde blood flow in the ascending aorta might be the persistence of antenatal circulatory alterations in favor of brain perfusion after birth. Fetuses with CHD often show signs of brain sparing [6,7,8], with fetuses with LSOL with retrograde blood flow being more affected than fetuses with LSOL with antegrade blood flow in the ascending aorta [9]. Furthermore, fetuses with CHD and a cerebroplacental ratio <1.0 (brain sparing) had higher cerebral blood flow after birth compared with fetuses with CHD and cerebroplacental ratio >1.0 [21].…”
Section: Discussionmentioning
confidence: 99%
“…Antenatally, normal distribution of oxygenated blood could be disturbed and vascular resistance may be altered in fetuses with CHD [3,6,7,8]. It has been reported that fetuses with left-sided obstructive lesions (LSOL) have lower pulsatility indices of the middle cerebral artery (MCA-PI) compared with fetuses without CHD [9].…”
Section: Introductionmentioning
confidence: 99%
“…1 Infants with congenital heart disease have abnormal and immature fetal brain development. 24 They often undergo palliative surgery requiring cardiopulmonary bypass in the neonatal period and then as infants and toddlers, during periods of critical brain development. These factors, along with repeated anesthetic exposure, abnormal cerebral perfusion pressures resulting from elevated central venous pressure, and long-term hospitalizations, increase the risk of shortand long-term neurodevelopmental, behavioral, and learning impairments.…”
Section: Discussionmentioning
confidence: 99%